Die sprachliche Analyse der niedergermanischen Votivformulare und Dedikantennamen, Fontes epigraphici religionum Celticarum antiquarum II: Provincia Germania inferior, Teilband 1 - DE BERNARDO-STEMPEL, PATRIZIA (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
Detailed diachronic analysis of the divine and personal names contained in the inscriptions with Celtic background found in Germania inferior (mostly edited with maps and photographs in the open-access data-base http://gams.uni-graz.at/context:fercan. With an appendix on the development of the Celtic branch from Indo-European. 63 ot the 100 divine names analysed are invocations to the Matres or Matronae.